Association between fingerprint patterns and intelligence quotient (IQ) - Sonia Nurul Ayunda; Syamsurizal S; Intan Fathia Rahmi; Dinda Nursal (Tropical Genetics, 2023)
Fingerprint pattern is a biological variation that differs from one racial group to another, between women and men and even identical twins. The formation and development of human fingerprints related to brain cells and nervous system associated with individual intelligence. The purpose in this research is to analyze the Association Between Fingerprint Patterns and Intelligence Quotient (IQ). This research method was carried out based on a systematic review with the analysis and search of this article using the PICO model with the PRISMA flowchart. According to the research, there is a substantial correlation between fingerprint patterns and intellectual intelligence (IQ).